DIGITAL TAXATION INNOVATION IN THE ERA OF ECONOMIC TRANSFORMATION: A COMPREHENSIVE ANALYSIS OF STRATEGICOPPORTUNITIES AND SYSTEMIC CHALLENGES TO ENHANCE EFFICIENCY AND OPTIMIZE NATIONAL REVENUE - Loso Judijanto; Renika Hasibuan; Rahma Helal Al_ Jbour; Dwi Koerniawati; Ignatius Septo Pramesworo (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Amid a transformative economic era, this groundbreaking study comprehensively analyzes digital taxation innovation. Delving into intricacies, it meticulously examines strategic opportunities and systemic challenges, emphasizing the integration of advanced data analytics, international collaboration, and public- private partnerships. Navigating the evolving fiscal landscape, the research enriches our understanding of efficiency enhancement and unveils novel approaches to optimizing national revenue. Beyond traditional boundaries, this exploration provides insights resonating with the dynamic interplay of technology and fiscal frameworks. As the digital era unfolds, the study contributes a nuanced perspective essential for policymakers, tax authorities, and stakeholders seeking a comprehensive grasp of the multifaceted dimensions of digital taxation.